Corporal Rhetoric : Regulating Reproduction in the Progressive Era - Schneider, Barbara (Barbara T.) (Book collections on Project MUSE., 2021)
"Examines public discourse from the Progressive Era over the state's right to regulate women's bodies and their reproduction"--